2011
DOI: 10.1111/j.1651-2227.2011.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional, socioeconomic and urban‐rural disparities in child and adolescent obesity in China: a multilevel analysis

Abstract: In contrast to most present-day high income countries, obesity among young people in China is associated with affluence and urban residence. Intervention and strategy for obesity prevention should be targeting high socioeconomic families in urban areas, perhaps with particular focus on boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
5
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 25 publications
5
36
5
4
Order By: Relevance
“…Similarly, a study conducted in Portugal claimed that age is not a risk factor for obesity (30). Some studies indicate that being overweight is more prevalent among children 7 -11 or 7 -12 years of age (14,25,28). The results of the studies on the relationship between age group and being obese or overweight are not consistent with ours.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Similarly, a study conducted in Portugal claimed that age is not a risk factor for obesity (30). Some studies indicate that being overweight is more prevalent among children 7 -11 or 7 -12 years of age (14,25,28). The results of the studies on the relationship between age group and being obese or overweight are not consistent with ours.…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly, other studies conducted in the same age group showed that males are more likely to be overweight than females (13,14,25,26). However, there are also studies claiming that obesity risk is higher in girls than boys (25,27,28). This study found no significant relationship between gender and obesity.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In countries at later stages of development, for example Mexico or Brazil, the socioeconomic (SES) pattern in overweight/obesity looks more like that of wealthy countries, where high-calorie foods are inexpensive and more likely to be available to low-income families [12]. In China, it is quite likely that these patterns are variable by the region of the country, so studies focusing on the whole country may exclude detail on important regional differences [13]. Complicating this picture is the variation between urban and rural settings in China, where residents of a city such as Shanghai are likely to have greater access to high-calorie foods.…”
Section: Introductionmentioning
confidence: 99%